2020
DOI: 10.1101/2020.07.03.182048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic analysis of the diversity, antimicrobial resistance and virulence potential of clinical Campylobacter jejuni and Campylobacter coli strains from Chile

Abstract: ABSTRACTCampylobacter jejuni and Campylobacter coli are the leading causes of human gastroenteritis in the developed world and an emerging threat in developing countries. There is increasing evidence that the incidence of campylobacteriosis in Chile and other South American countries is greatly underestimated, mostly due to the lack of adequate diagnostic methods. Accordingly, there is limited genomic and epidemiological dat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 74 publications
(161 reference statements)
1
4
0
Order By: Relevance
“…For the current study, four clonal lineages (CC-21, CC-42, CC-48 and CC-52) were found in common between the strains isolated from beef liver and the clinical strains previously reported in Chile (Collado et al 2018;Bravo et al 2021), which suggests a zoonotic transmission.…”
Section: Genotypingsupporting
confidence: 66%
See 4 more Smart Citations
“…For the current study, four clonal lineages (CC-21, CC-42, CC-48 and CC-52) were found in common between the strains isolated from beef liver and the clinical strains previously reported in Chile (Collado et al 2018;Bravo et al 2021), which suggests a zoonotic transmission.…”
Section: Genotypingsupporting
confidence: 66%
“…Recently, Bravo et al . (2021) also reported finding the operon encoding for this pump, in all the Chilean clinical strains they analysed.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations